321 Subjective Sleep and NEO Five Factor Personality Domains in Individuals with Primary Insomnia Compared to Good Sleeper Controls. (3rd May 2021) - Orff, Henry; Rivera, Guadalupe; Almklov, Erin
Abstract: Introduction: Insomnia is a common sleep disorder in adults. Primary Insomnia (PI) can be specified in cases where the insomnia symptoms cannot be overtly attributed to medical, psychiatric, or environmental reasons. Although the underlying predisposing causes of insomnia are unclear, one possible contributing factor may be personality traits. To date no consensus on the relationship between insomnia and personality has been determined, although many studies have found a general association with neuroticism. To better explore these associations, this study compared NEO Five Factor Model (FFM) personality traits with measures of subjective sleep in PIs and Good Sleeper (GS) controls. Methods: Nine PI and nine GS matched for age, sex, and education were studied. Each participant was administered the Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), and NEO FFM. Participants also completed a sleep diary for 1-week. ANOVAs compared PI vs GS on ISI, PSQI, NEO FFM, and 7-day averaged data from the sleep diary. Lastly, sleep variables were collapsed across groups and Pearson correlations were run to explore the relationship between sleep and personality. Results: PIs (4M/5F, age=39.6+/-10.1, education=16.0+/-1.7) and GSs (4M/5F, age=38.6+/-7, education=15.1+/-1.5) showed significant differences in ISI (p<.001) and PSQI (p<.001) total scores. Additionally, the groups differed on diary measures of total sleep (p=.001), sleep efficiency (SE: p<.001), sleep latency (p=.005), and wake after sleep onset (p<.001). On the NEO FFM only the Agreeableness domain was found to differentiate the two groups (p=.004). Pearson correlations found significant negative relationships for Agreeableness with ISI (r= -.625/p=.006), PSQI (r= -.611/p=.007), and a significant positive relationship with SE from the sleep diary (r=.602/p=.008). Conclusion: In a small but well-matched study of PI and GS, significant differences in Agreeableness on the NEO FFM were observed. Lower levels of agreeableness were associated with poorer sleep on the ISI and PSQI, and lower SE on the sleep diaries. Unlike other published reports this study did not find a relationship between insomnia and neuroticism, which may reflect the use of a well-screened Primary Insomnia sample with limited comorbidities. Future research should determine if other insomnia subtypes (e.g., psychophysiological, paradoxical insomnia) are associated with different personality profiles. Support (if any):